A PERCEPÇÃO DOS PROFESSORES SOBRE O ENSINO DE CIÊNCIAS PARA ALUNOS COM DEFICIÊNCIA INTELECTUAL: UM ESTUDO NA EDUCAÇÃO BÁSICA - Matos, Francisca Eládia Cavalcante de Abrantes (2024)
The present study is part of the research line Teacher Training in Science and Mathematics, of the Postgraduate Program in Science and Mathematics Teaching, within the scope of the Academic Master's Degree, at the Franciscan University of Santa Maria (RS). Exploring this universe of science is a fascinating journey full of discoveries, because teaching is not limited to textbooks, it also involves direct observation of the natural world. Science is constantly evolving, so it is important that students understand the dynamic nature of this scientific knowledge. Given this, the present work aims to investigate how specialized educational services, centered on science teaching, occur in schools in the state network of Boa Vista, capital of Roraima, considering students with intellectual disabilities. To this end, the methodology was characterized as documentary research, with a qualitative teaching approach. The target audience for the investigation were teachers in training and in practice (assistants), as well as educational managers, interested in promoting inclusive and accessible scientific education for all students, including those with disabilities. To meet the specific objectives of the work, firstly, a study was carried out on teaching in basic education in the state network of Boa Vista RR, understanding the specificities of special education in basic training. Next, considering that Special Education, from the perspective of inclusive Education, based on philosophical, political and legal principles of human rights, comprises the change in pedagogical conception, teacher training and educational management to realize everyone's right to education, a study was carried out on the assistance to students with disabilities, based on the National Common Curricular Base and Science Teaching in Basic Education. Finally, the importance of teacher training in Science teaching was analyzed, with the research focused on schools in the state education network in the capital Boa Vista, in Roraima, which serve students, identified as People with Disabilities (PcD), whose spaces have multifunctional rooms or resource rooms, which are environments that offer the aforementioned specialized educational service. It was found that this service is different from the conventional classroom service, and each student has their own plan, with a plan that respects their unique characteristics and needs. Therefore, depending on these needs, this plan is adapted with objectives and activities aimed at providing assistance.It was inferred that the service, contained in the schools' Pedagogical Proposal, also aims at family involvement and participation, to guarantee full access and participation of the target audience of Special Education, above all, to carry out coordination to meet all the specificities of the target audience. In this context, the inclusive development of schools assumes the centrality of public policies to ensure access, participation and learning conditions for students in state public schools, with equal conditions.